Crystal Structures of Arabidopsis thaliana GDP-D-Mannose Pyrophosphorylase VITAMIN C DEFECTIVE 1 - Zhang, Chi; Zhao, Shun; Li, Yu-Shuai; He, Chao; Wang, Xiao; Liu, Lin (Frontiers in Plant Science, 2022)
Plant GDP-D-mannose pyrophosphorylase (GMPase) catalyzes a committed step in ascorbic acid biosynthesis pathway. Arabidopsis thaliana VTC1 is the first genetically characterized plant GMPase and has unique properties when compared with bacterial and animal homologs. Here we present the crystal structures of VTC1 in the unliganded and product-bound states at resolutions of 2.8 and 3.0 Å, respectively. VTC1 dimerizes in a same way like other known GMPases, but dodecamerizes in a previously unobserved arrangement. The interactions to GDP-D-mannose and inorganic pyrophosphate are revealed by the product-bound VTC1 structure. An in vitro GMPase activity assay confirms the regulatory role of the C-terminal left-handed β-helix domain, and structural analyses suggest the models of VTC1 hetero-complex with its interacting proteins. The structural information advances our insights into the different mechanisms involved in VTC1 regulation.